Vertical‐Switching Conductive Bridge Random Access Memory with Adjustable Tunnel Gap and Improved Switching Uniformity Using 2D Electron Gas - Jiho Kim; Ohhyuk Kwon; Jongseon Seo; Hyunsang Hwang (Advanced Electronic Materials)
Abstract Owing to the high reactivity and diffusivity of Ag and Cu ions, controlling the atomic filament formation and rupture processes in conductive bridge random‐access memory (CBRAM) is challenging. In this study, it is demonstrated that by using a 2D electron gas (2DEG) as the bottom electrode (BE) in a vertical‐switching CBRAM (V‐CBRAM), filament formation and rupture can be effectively managed and the tunnel gap distance created by partial filament formation can be adjusted. The 2DEG BE induces partial filament formation by limiting the number of electrons required for this process in the V‐CBRAM device, as verified via current fitting to the quantum point contact model. Varying the electron concentration and activation energy for electrons trapped in the 2DEG, when paired with various programming voltages, leads to transitions in the device resistance state via changes in the distance of the tunnel gap. This tunnel‐gap‐tunable 2DEG V‐CBRAM device, which exhibits superior switching uniformity, can be employed for nonvolatile memory applications in the sub‐G0 conductance regime, such as 3‐bit multilevel cells and selector‐less memory.